Centring the voices of survivors of child sexual abuse in research: an act of hermeneutic justice - Alyce, Susanna; Taggart, Danny; Sweeney, Angela (Frontiers in Psychology, 2023)
Survivors of child sexual abuse (CSA) are known to hold silence and create distance between themselves and service providers for self-protection, as groomed behaviour or to protect the listener from vicarious trauma. Silence for many survivors has also been reinforced as a beneficial action by previous experiences of disclosing and being rejected, challenged or disbelieved. How can researchers be sure the same dynamic is not playing out in research interviews? Generating reliable research data is an imperative and an act of epistemic justice that enables CSA survivors to testify to the suffering caused by abuse, subsequent trauma distress and to contribute to social discourse for change. Fricker, however, notes that the precursor to testimonial justice is hermeneutic justice. Hermeneutic justice pivots on the dual action of accurate understanding and interpretation, but CSA experiences may be beyond the comprehension of untraumatised listeners, because their own frame of reference renders them unable or unwilling (even if unconsciously) to entertain the truth of such human depravity and cruelty. If survivors are not understood, their testimonies can be misconstrued or oftentimes excluded from the generation of epistemic knowledge, leaving the survivor unable to make sense of, and process, their experiences. These are crucial issues for researchers in the field of CSA and other crimes of sexual and gendered abuse. This paper considers the operationalisation of a participatory research approach held within a Lived Experience research paradigm. Such methodologies advocate for peer involvement, which is becoming more widely recognised as supporting testimonial justice, and the accurate understanding and interpretation of survivors’ testimonies. The issue of validating the methodology and methods is considered, exploring a rigorous data audit and researcher reflexivity as contributors to trustworthy data. Peer and participant safety when researching through Lived Experience is addressed. Data from a doctoral research study is used to illustrate this paper.